(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This material describes the passage of the artist Jaider Esbell (1979-2021) and his partner, grandmother Bernal (1945 - 2020), in the year 2019, through the “Rios, roças e redes” Project of the Jardinidades event, produced by SESC/SP. It is intended to investigate whether the actions proposed by the artists can compose with the thought on cosmopolitics (Stengers, 2018), as a link of responsibility between humans and non-humans from symbolic experiences pertinent to the field of art.